The tolerability of single low dose primaquine in glucose-6-phosphate deficient and normal falciparum-infected Cambodians - Lek Dysoley; Saorin Kim; Sergio Lopes; Nimol Khim; Steven Bjorges; Samphornarann Top; Chea Huch; Huy Rekol; Nelli Westercamp; Mark M. Fukuda; Jimee Hwang; Arantxa Roca-Feltrer; et al. (BMC Infectious Diseases, 2019)
Abstract Background The WHO recommends single low-dose primaquine (SLDPQ, 0.25 mg/kg body weight) in falciparum-infected patients to block malaria transmission and contribute to eliminating multidrug resistant Plasmodium falciparum from the Greater Mekong Sub region (GMS). However, the anxiety regarding PQ-induced acute haemolytic anaemia in glucose-6-phosphate dehydrogenase deficiency (G6PDd) has hindered its use. Therefore, we assessed the tolerability of SLDPQ in Cambodia to inform national policy. Methods This open randomised trial of dihydroartemisinin-piperaquine (DHAPP) + SLDPQ vs. DHAPP alone recruited Cambodians aged ≥1 year with acute uncomplicated P. falciparum. Randomisation was 4:1 DHAPP+SLDPQ: DHAPP for G6PDd patients and 1:1 for G6PDn patients, according to the results of the qualitative fluorescent spot test. Definitive G6PD status was determined by genotyping. Day (D) 7 haemoglobin (Hb) concentration was the primary outcome measure. Results One hundred nine patients (88 males, 21 females), aged 4–76 years (median 23) were enrolled; 12 were G6PDd Viangchan (9 hemizygous males, 3 heterozygous females). Mean nadir Hb occurred on D7 [11.6 (range 6.4 ─ 15.6) g/dL] and was significantly lower (p = 0.040) in G6PDd (n = 9) vs. G6PDn (n = 46) DHAPP+SLDPQ recipients: 10.9 vs. 12.05 g/dL, Δ = -1.15 (95% CI: -2.24 ─ -0.05) g/dL. Three G6PDn patients had D7 Hb concentrations < 8 g/dL; D7-D0 Hbs were 6.4 ─ 6.9, 7.4 ─ 7.4, and 7.5 ─ 8.2 g/dL. For all patients, mean (range) D7-D0 Hb decline was -1.45 (-4.8 ─ 2.4) g/dL, associated significantly with higher D0 Hb, higher D0 parasitaemia, and receiving DHAPP; G6PDd was not a factor. No patient required a blood transfusion. Conclusions DHAPP+SLDPQ was associated with modest Hb declines in G6PD Viangchan, a moderately severe variant. Our data augment growing evidence that SLDPQ in SE Asia is well tolerated and appears safe in G6PDd patients. Cambodia is now deploying SLDPQ and this should encourage other GMS countries to follow suit. Trial registration The clinicaltrials.gov reference number is NCT02434952.